P(x) = x^3 + ax^2 + bx + 6
________________________________
Reminder :
x - a = 0 ==》 x = a
P(a) = Reamaining of the diving P(x) by
( x - a )
________________________________
x - 2 = 0 ==》x = 2 ==》P(2) = 0
(2)^3 + a(2)^2 + b(2) + 6 = 0
8 + 4a + 2b + 6 = 0
4a + 2b + 14 = 0
4a + 2b + 14 - 14 = 0 - 14
4a + 2b = - 14
( 4a + 2b ) ÷ 2 = ( -14 ) ÷ 2
2a + b = - 7 ( ♡ )
_________________________________
x - 3 = 0 ==》 x = 3 ==》P(3) = 3
(3)^3 + a(3)^2 + b(3) + 6 = 3
27 + 9a + 3b + 6 = 3
9a + 3b + 33 = 3
9a + 3b + 33 - 33 = 3 - 33
9a + 3b = - 30
( 9a + 3b ) ÷ 3 = ( - 30 ) ÷ 3
3a + b = - 10 ( ☆ )
________________________________
( ♡ ) , ( ☆ ) in pair system of equation
( ☆ ) : 3a + b = - 10 3a + b = - 10
====》
( ♡ ) : 2a + b = - 7 × (-1) - 2a - b = + 7
___________ +
a = - 3
So :
2( - 3 ) + b = - 7
- 6 + b = - 7
- 6 + 6 + b = - 7 + 6
b = - 1
¥¥¥¥¥¥¥¥¥¥¥¥¥¥¥¥¥¥¥¥¥¥¥¥¥¥¥¥¥¥
Thus : a = - 3 & b = - 1